1982
DOI: 10.1089/jir.1982.2.195
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prolonged Administration of Interferon-Alpha on Pharmacokinetics, Fever, Lymphocyte Proliferative Response, and NK Cell Activity

Abstract: Over a 60-week period, a patient with multiple warts received a total of 281 x 10(6) units of human leukocyte interferon (IFN-alpha) by intramuscular (IM) or intralesional (IL) injections. Circulating IFN was significantly higher following IM administration than after IL administration. These pharmacokinetics did not change. The patient's body temperature was always significantly elevated after administration of IFN. However, hyporeactivity to the febrile response developed when the interval between repeated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…To determine perturbations in the NK system, measurements of cytotoxic activity of the peripheral leukocytes may be inadequate. We have previously found that, despite' normal circulating activity, the capacity of the NK activity of mononuclear leukocytes to be enhanced by interferon may be depressed (3,11). Also, we noted in mice that CyA can block the ability of interferon to enhance NK activity (6) without affecting Nk activity itself.…”
mentioning
confidence: 92%
“…To determine perturbations in the NK system, measurements of cytotoxic activity of the peripheral leukocytes may be inadequate. We have previously found that, despite' normal circulating activity, the capacity of the NK activity of mononuclear leukocytes to be enhanced by interferon may be depressed (3,11). Also, we noted in mice that CyA can block the ability of interferon to enhance NK activity (6) without affecting Nk activity itself.…”
mentioning
confidence: 92%